Characterization of Candida Species Isolated from cases of Vulvovaginitis in women referring to selected gynecological clinics - Batol Bonyadpour; Marzieh Akbarzdeh; Abdol Ali Mohagheghzadeh (Mashhad University of Medical Sciences, 2016)
Background and aim: About 20% of non-pregnant women aged 15 to 55 harbour Candida albicans in the vagina .the aimed to determine the Characterization of Candida Species Isolated from women with Vulvovaginitis candidates (VVC) of reproductive ages. Methods: this descriptive study was conducted on 280 of who were selected for gathering samples by Purposive sampling based on their history and characteristics of vaginal discharges in 2009. Among these patients, 105 ones were diagnosed with candidiasis. The data were collected using demographic information form and disease symptoms. the species were differentiated using germ tube test, chrome agar test, and chlamidospore test. Data analysis was performed in SPSS V.16, using Descriptive Statistics Results: the prevalence of candida vaginitis was 9.3%.105 samples obtained from patients.. Chlamidospore was detected in 54.3% of the corn meal agar media. Besides, in chrome agar test, 41.9% of the samples turned into green representing candida albicans. In germ tube test, on the other hand, 70.5% of the samples were candida albicans, while 29.5% were candida non-albicans. Overall, The frequency of the Candida albicans, Candida glabrata, Candida tropicalis and  the Candida Krusei were  66.6% , 219%  , 8.6% ,  and 2.9%, respectively. Conclusion: Candida albicans was the most common species leading to the Vulvovaginitis in patients with VCC while other species were at the secondary importance stages.Due to inaccurate diagnosis of the disease based on the clinical symptoms, fungal culture is recommended as a standard diagnostic method.